Committee report: Publication guidelines and recommendations for studies using electroencephalography and magnetoencephalography. (22nd October 2013) - Keil, Andreas; Debener, Stefan; Gratton, Gabriele; Junghöfer, Markus; Kappenman, Emily S.; Luck, Steven J.; Luu, Phan; Miller, Gregory A.; Yee, Cindy M.
Abstract Electromagnetic data collected using electroencephalography (EEG) and magnetoencephalography (MEG) are of central importance for psychophysiological research. The scope of concepts, methods, and instruments used by EEG/MEG researchers has dramatically increased and is expected to further increase in the future. Building on existing guideline publications, the goal of the present paper is to contribute to the effective documentation and communication of such advances by providing updated guidelines for conducting and reporting EEG/MEG studies. The guidelines also include a checklist of key information recommended for inclusion in research reports on EEG/MEG measures.